HEDONISME KONSUMEN SEBAGAI VARIABEL MEDIATOR ANTARA PEMASARAN DAN PEMBELIAN TIDAK TERENCANA - Satriawan, Stevanus Bayu; Hartoyo, Hartoyo; Yuliati, Lilik Noor (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2015)
In a process of purchase, consumers can conduct planned purchase or unplanned purchase behavior. Unplanned purchase behavior, also known as impulsive purcahse behavior, refers to consumers’ response to marketing of product that is not extremely expensive including bakery product. Product and marketing factors, and also consumers’ characteristics are identified as determinant factors of unplanned purchase behavior. This research aimed to examine influence of marketing factors and consumer hedonism on unplanned purchase behavior of consumers of bakey outlet that was located in one of shopping center in the city of Bekasi. The sampling in this research used non-probability sampling. The number of the respondents was 192 people that became consumers of ABC bakery outlet. The analysis data used Structural Equation Modelling (SEM). Theresult showed that product and marketing indicator were significant indicators of latent variable of marketing factors (marketing mix). Moreovver, marketing factors had direct influence on consumer hedonism and unplanned purchase behavior positive significantly. Marketing factors also influenced indirectly on unplanned purchase behavior positive significantly; with consumer hedonism as mediator variable.